The Role of the Effects of Autophagy on NLRP3 Inflammasome in Inflammatory Nervous System Diseases - Zhao, Shizhen; Li, Xiaotian; Wang, jie; Wang, Honggang (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is a self-sustaining process of internal environment stability in eukaryotic cells. In this process, pathogens, abnormal proteins and organelles are wrapped in double-layer membranes to form autophagosomes, which are then transferred to lysosomes for degradation. Autophagy participates in a variety of physiological and pathological processes. Nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome, containing NLRP3, apoptosis associated speck like protein (ASC) and pro-caspase-1, can activate caspase-1 to lead to pyroptosis and induce the maturation and secretion of interleukin-1β (IL-1β) and IL-18. NLRP3 inflammasome is related with many diseases. In recent years, it has been reported that autophagy plays an important role by influencing NLRP3 inflammasome in many diseases including inflammatory nervous system diseases. In this review, we summarized the recent studies about the effects of autophagy on NLRP3 inflammasome in inflammatory nervous system diseases to provide ideas for the relevant basic research in the future.